2020
DOI: 10.48550/arxiv.2006.06334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Ray-Knight representation of up-down Chinese restaurants

Abstract: We study composition-valued continuous-time Markov chains that appear naturally in the framework of Chinese Restaurant Processes (CRPs). As time evolves, new customers arrive (up-step) and existing customers leave (down-step) at suitable rates derived from the ordered CRP of Pitman and Winkel (2009). We relate such up-down CRPs to the splitting trees of Lambert (2010) inducing spectrally positive Lévy processes. Conversely, we develop theorems of Ray-Knight type to recover more general up-down CRPs from the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Indeed, Shiga's approach could be understood as spindles-without-scaffolding. As discussed in [20,41], this scaffolding can be interpreted as representing a self-similar genealogy among spindles.…”
Section: 3mentioning
confidence: 99%
“…Indeed, Shiga's approach could be understood as spindles-without-scaffolding. As discussed in [20,41], this scaffolding can be interpreted as representing a self-similar genealogy among spindles.…”
Section: 3mentioning
confidence: 99%
“…The construction and analysis of ordered analogues of Petrov's [15] two-parameter extension of Ethier and Kurtz's [3] infinitely-many-neutral-alleles diffusion model has recently attracted significant interest in the literature [7,8,20,21,23]. Recall that the EKP(α, θ) diffusions constructed in [15] are a family of Feller diffusions on the closure of the Kingman simplex…”
Section: Introductionmentioning
confidence: 99%
“…Let (X (α,θ) n (k)) k≥0 be a Markov chain on C n with transition kernel T (α,θ) n defined as in Equation (1) using the p ↑ (α,θ) and p ↓ just described. A Poissonized version of this chain was considered in [21,23]. It can be shown that X (α,θ) n is an aperiodic, irreducible chain.…”
Section: Introductionmentioning
confidence: 99%
“…We will address the remaining cases in a sequel paper [39], where we take a third approach to the threeparameter family. This involves the development of a limit theory for composition-valued Markov chains, which is of independent interest, and which in the two-parameter special case resolves a conjecture of [35]. See also [34] for a different approach to convergence results in the corresponding de-Poissonized setting, enhancing [27].…”
Section: Introductionmentioning
confidence: 99%